Professional ethics of the bar - Anand, C. L. (Allahabad, 1987)
Ethics is nothing but, broadly stated, the idea of what is right and what is wrong in conduct. This is largely learnt and imbibed during up bringing whether in a family, or society or trade or profession. What is the necessity of a book, then, when ethics can be learnt and imbibed while being brought up in a profession like law, noble and honourable, one may ask. It is the practice of ethics that has made the profession noble and honourable. Rules of ethics are the most precious heritage of the Bar, and it is due to the Code of its ethics governing the relations between lawyers interse and vis-a-vis others during the course of the centuries that greatness and honour came to be acquired by the legal profession gradually, imperceptibly, but surely.
Keywords: Law and ethics